Tunnel on East Second Street which is to be closed, 1958. - (:unkn) unknown (Forsyth County Public Library, 2009)
WSJ 6-8-58 p.1B.
Tunnel on East Second Street which is to be closed, 1958.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth